Piezoelectric Vibration Energy Harvesting Modeling & Experiments - Rafique, Sajid (Springer International Publishing, 2018)
The electromechanical coupling effect introduced by piezoelectric vibration energy harvesting (PVEH) presents serious modeling challenges. This book provides close-form accurate mathematical modeling and experimental techniques to design and validate dual function PVEH vibration absorbing devices as a solution to mitigate vibration and maximize operational efficiency. It includes in-depth experimental validation of a PVEH beam model based on the analytical modal analysis method (AMAM), precisely identifying electrical loads that harvest maximum power and induce maximum electrical damping. The author's detailed analysis will be useful for researchers working in the rapidly emerging field of vibration based energy harvesting, as well as for students investigating electromechanical devices, piezoelectric sensors and actuators, and vibration control engineering. Includes a thorough theoretical and experimental analysis of a PVEH beam or assembly of beams; Provides an in-depth investigation of a dual function piezoelectric vibration energy harvester beam/tuned vibration absorber (PVEH/TVA) or "electromechanical TVA"; Outlines the electromechanical TVA's potential application to dual-function energy harvesting and vibration control; Establishes a procedure for the exact modeling of PVEH beams, and assemblies of such beams, using the dynamic stiffness matrix (DSM) method. The book contains useful MatLab program codes which model complex equations, providing a deeper and quicker insight of the PVEH as well as the dual function PVEH/TVA systems.